RANCANG BANGUN SISTEM PENGINGAT JADWAL PEMBAYARAN SPEEDY BERBASIS SMS GATEWAY (Information Technology and Telematics, 2015)
Abstrak :~~ PT.TELKOM is a company engaged in telecommunications owned by the state. telecoms possess many prodak that can be enjoyed by the public one that is speedy. a speedy internet service prodak using cable media. of the research that has been conducted found that the telecoms do not yet have a reminder system that can provide information to users or customers regarding billing amount speedy, therefore the presence of the case can be made that the payment schedule reminder system automatically uses the SMS gateway. some of which can be applied in the system including through automatic text message that contains the payment schedule and the amount of speedy monthly bill   Keywords : ~~telkom, sms, sms gateway